Analisis Kontroversi Pasal Kohabitasi (Hidup Bersama Tanpa Nikah) dalam KUHP Baru dalam Perspektif Hukum Islam - Satriani Satriani (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
The regulation of cohabitation in Law Number 1 of 2023 concerning the Criminal Code (KUHP) represents a form of national criminal law reform that continues to spark debate, particularly regarding the protection of privacy rights, moral values, and alignment with Islamic law. This study aims to analyze the regulation of cohabitation within the National Criminal Code and examine its compatibility with Islamic legal principles. The research employs a normative legal research method, utilizing both statutory and conceptual approaches. Legal materials consist of primary sources—comprising legislation and Islamic legal sources—and secondary sources, such as literature, scholarly journals, and expert opinions, all of which were analyzed qualitatively. The findings indicate that Article 412 of the Criminal Code classifies cohabitation as an absolute complaint-based offense, restricting law enforcement action to cases initiated by specific parties; this reflects a balance between protecting public morality and respecting the private sphere. From an Islamic legal perspective, cohabitation is a prohibited act, as it is viewed as a pathway to adultery (*muqaddimah al-zina*) and conflicts with the objectives of *maqāṣid al-sharī'ah* (the higher objectives of Sharia), specifically the preservation of lineage (*ḥifẓ al-nasl*) and honor (*ḥifẓ al-'irdh*). Thus, the regulation of cohabitation in the National Criminal Code demonstrates a harmonization between positive law and the Islamic legal values ​​prevalent in Indonesian society.